Design and implementation of real-time on-board satellite image correction algorithms on a programmable logic platform - Twilley, Rowan (Stellenbosch : Stellenbosch University, 2025)
Twilley, R. 2025. Design and implementation of real-time on-board satellite image correction algorithms on a programmable logic platform. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/ad517ab4-97ad-4455-b497-045e676332c4